Factors Associated with the Occurrence of Post Intensive Care Syndrome in Patients Post Ventilator Use at PMI Hospital Bogor in 2023 - Yusdi Ghazaly (Westscience Press, 2023)
Post-ventilator patients can experience Post Intensive Care Syndrome (PICS) problems. This includes physical, psychological and cognitive changes. This research aims to analyze the incidence of PICS in post-ventilator patients in Surabaya. The design of this study used a descriptive research method with research variables including physical, psychological and cognitive health. The population of post-ventilator patients amounted to 56 patients with a sample of 49 patients using the simple random sampling technique. The instrument used in this study was a questionnaire sheet. Which consists of 16 questions, divided into physical, psychological and cognitive aspects. Post intensive care syndrome in post-ventilator patients, the majority of the physical aspects are in the sufficient category, such as changes in fatigue and pain. In the psychological (mental) aspect, most are in the sufficient category marked by anxiety and sadness. The cognitive aspect is also mostly in the sufficient category which includes changes in patient memory. Post intensive care syndrome in the physical, psychological and cognitive aspects is in the sufficient category. This is marked by mild changes. The recommendation in this study is that patients need to get health education only if they experience PICS.